MODEL DETERMINAN KINERJA GURU BERDASARKAN KEPEMIMPINAN KEPALA SEKOLAH, KOMUNIKASI ORGANISASI, DAN MOTIVASI KERJA GURU DI SEKOLAH DASAR NEGERI KECAMATAN DRAMAGA - Riswan Firmansyah; Yulita Pujilestari; Imas Masriah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the determinants of teacher performance based on principals' leadership, organizational communication, and teachers' work motivation in public elementary schools in Dramaga District. The study employed a quantitative approach using a survey method. The research population consisted of 328 teachers, with a sample of 180 teachers. The results showed that principals' leadership had a positive and significant relationship with teacher performance (r = 0.616; R² = 0.379; p = 0.004). Organizational communication also had a positive and significant relationship with teacher performance (r = 0.456; R² = 0.208; p = 0.036). Teachers' work motivation demonstrated a positive and significant relationship with teacher performance and emerged as the most dominant variable (r = 0.634; R² = 0.402; p < 0.001). Simultaneously, principals' leadership, organizational communication, and teachers' work motivation had a positive and significant effect on teacher performance (F = 8.203; p < 0.001), with a coefficient of determination of R² = 0.423, indicating that the three variables jointly explained 42.3% of the variance in teacher performance. These findings suggest that strengthening teachers' work motivation, enhancing principals' leadership, and improving organizational communication are essential factors in improving teacher performance.